CHARACTERISATION OF TABLETS FOR DEFECT IDENTIFICATION USING IMAGE PROCESSING TECHNIQUES FOR QUALITY CONTROL IN PHARMACEUTICAL INDUSTRY - Karthik, Durga; K, Vijayarekha; K, Surya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Our aim is to characterize the parameters for identifying defective tablets from the manufacturing line using image processing techniques. Methods: Manufactured tablets might have defects such as broken chips, missing tablet, and color variation. Images of tablets are captured using machine vision camera. The features are detected using feature extraction for a tablet without defects and are stored in a database. The stored details are used for identifying defective tablets during manufacturing. Results: The characteristics such as color, shape, number of pills, area, and perimeter of the normal tablets without defects were extracted. Conclusion: The defective tablets can be identified by comparing the characteristics stored in the database and can be removed effectively.